2020
DOI: 10.1002/erv.2732
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between reward sensitivity, impulsivity, and food addiction: A systematic review

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 93 publications
(35 reference statements)
2
50
0
Order By: Relevance
“…Our data showed that the self-reported psychological impact of the COVID-19 was positively correlated ( Supplementary Table 1) with alcohol problems (small effect size), SMA symptoms (medium to large effect size) and FA symptoms (medium effect size). At a multivariate level, when controlling for potential confounding variables that have been traditionally related to addictive disorders [e.g., impulsivity (46)(47)(48)], the IES-R remained independently associated with CAGE, BSMAS, and mYFAS 2.0 total scores. However, neither self-reported COVID-19 related distress, nor the other variables related to this emergency (e.g., isolation/quarantine) were significantly associated with increased CAGE total score variability.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the self-reported psychological impact of the COVID-19 was positively correlated ( Supplementary Table 1) with alcohol problems (small effect size), SMA symptoms (medium to large effect size) and FA symptoms (medium effect size). At a multivariate level, when controlling for potential confounding variables that have been traditionally related to addictive disorders [e.g., impulsivity (46)(47)(48)], the IES-R remained independently associated with CAGE, BSMAS, and mYFAS 2.0 total scores. However, neither self-reported COVID-19 related distress, nor the other variables related to this emergency (e.g., isolation/quarantine) were significantly associated with increased CAGE total score variability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the facets of impulsive behavior are dictated by different neural circuits and are thought to reflect uncorrelated phenotypes (Barrus et al, 2015;Dougherty et al, 2009;Nautiyal et al, 2017;Reynolds et al, 2008). However, multiple facets of impulsivity have been identified as having a relationship with over-eating in humans, including non-planning impulsivity, attentional impulsivity, and motor impulsivity (Garza et al, 2016;Georgii et al, 2017;Maxwell, Gardiner, & Loxton, 2020). This relationship has also been observed within rodents as well, with high impulsive rats engaging in more "binge-like" and excessive consumption of highly palatable foods (Anastasio et al, 2019;Velázquez-Sánchez et al, 2014), potentially due to convergent neurocircuitry of the ventromedial prefrontal cortex (Anastasio et al, 2019).…”
Section: Delay Discountingmentioning
confidence: 99%
“…For example, patients with EDs who have problems pursuing tasks to the end and focusing on long-term goals are more likely to develop addiction-like eating patterns [ 100 ]. A recent systematic review reported that across 45 studies, impulsivity was consistently associated with FA [ 101 ]. Given that FA has been reported as a mediator between impulsivity and obesity [ 102 ], it is possible that in certain susceptible individuals, ED behaviors develop along this trajectory to suppress unwanted weight.…”
Section: Substance Use Disordersmentioning
confidence: 99%